Does gender diversity in the workplace mitigate climate change? - Yener Altunbaðs; Leonardo Gambacorta; Alessio Reghezza; Giulio Velliscig (European Central Bank (ECB), 2022)
We match firm-corporate governance characteristics with firm-level carbon dioxide (CO2) emissions over the period 2009-2019 to study the relationship between gender diversity in the workplace and firm carbon emissions. We find that a 1 percentage point increase in the percentage of female managers within the firm leads to a 0.5% decrease in CO2 emissions. We document that this effect is statically significant, also when controlling for institutional differences caused by more patriarchal and hierarchical cultures and religions. At the same time, we show that gender diversity at the managerial level has stronger mitigating effects on climate change if females are also well-represented outside the organization, e.g. in political institutions and civil society organizations. Finally, we find that, after the Paris Agreement, firms with greater gender diversity reduced their CO2 emissions by about 5% more than firms with more male managers.
Keywords: G12; G23; G30; D62; Q54; 330; Carbon emissions; Female managers; Global warming; Paris Agreement; Green economics